Crystal structure of 2-cyclohexyl-1,3-thiazolo[4,5-b]pyridine - El-Hiti, Gamal A. (Acta Crystallogr E Crystallogr Commun, 2015)
In the title compound, C(12)H(14)N(2)S, the cyclohexane ring adopts a chair conformation with the exocyclic C—C bond in an equatorial orientation. The mean plane through the cyclohexane ring (all atoms) is twisted from the thiazolopyridine ring system (r.m.s. deviation = 0.013 Å) by 39.57 (6)°. In the crystal, molecules form (100) sheets, although there are no specific directional interactions between them. The crystal stucture was refined as a two-component perfect twin.